HOW RESILIENCE ENGINEERING MAINTAINS SUSTAINABLE VALUE. Issue 2 (July 2016) - Jackson, Scott
ABSTRACT: The purpose of this essay is to show that the concept of the resilience of an engineered system is in agreement with the concept of sustainable value. The INCOSE Resilient Systems website (INCOSE 2015) defines the resilience of an engineered system as "the ability to provide required capability in the face of adversity. Similarly sustainable value has its roots in economics. According to (Hart and Milstein 2003), a sustainable enterprise "is one that contributes to sustainable development by delivering simultaneously economic, social, and environmental benefits — the so‐called triple bottom line." So to the extent that capability is aligned with stakeholder value, resilience supports the goal of sustainable value. Capability may be some degree of system performance or simply sustaining human life following an encounter with a threat. Adversity can be external or internal threats. External threats can be natural, such as earthquakes, or human‐made such as terrorist attacks. Internal threats may be human error or software faults.